Effect of SSI on Vibration Control of Structures with Tuned Vibration Absorbers - Said Elias (Shock and Vibration)
This paper investigates the effect of considering soil-structure interaction (SSI) in seismic responses of reinforced concrete (RC) chimneys installed by distributed tuned vibration absorbers vertically (d-MTVAs). A multimode control approach is used to design the d-MTVAs. Two-dimensional (2D) RC chimney is the assembly of beam elements. Frequency-independent constants for the springs and dashpots are used for modeling the raft and the surrounding soil. The equations of motion for nonclassically damped systems are derived and solved using Newmark’s method. The effectiveness of the d-MTVAs is weighed against the case of single tuned vibration absorber (STVA), d-MTVAs suppressing the first modal responses (d-MTVAs-1), and randomly distributed MTVAs (ad-MTVAs). Additionally, parametric studies are conducted for varying mass and damping ratios in the STVA, d-MTVAs-1, ad-MTVAs, and d-MTVAs. In order to show the efficiency in the STVA, d-MTVAs-1, ad-MTVAs, and d-MTVAs cases, responses (displacement and acceleration) at top of the RC chimney while subjected to different real earthquake excitations are computed. It is concluded that the STVA, d-MTVAs-1, ad-MTVAs, and d-MTVAs are effective in response mitigation of the RC chimney; however, d-MTVAs are more efficient while considering equal total mass of the TVA(s). Moreover, the soil type significantly influenced the design parameters of the STVA/d-MTVAs-1/ad-MTVAs/d-MTVAs and seismic response of the RC chimney.